2003
DOI: 10.1038/nmat859
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition at the percolation threshold in epitaxial (La0.7Ca0.3MnO3)1–x:(MgO)x nanocomposite films

Abstract: 'Colossal magnetoresistance' in perovskite manganites such as La0.7Ca0.3MnO3 (LCMO), is caused by the interplay of ferro-paramagnetic, metal-insulator and structural phase transitions. Moreover, different electronic phases can coexist on a very fine scale resulting in percolative electron transport. Here we report on (LCMO)1-x:(MgO)x (0 < x < or = 0.8) epitaxial nano-composite films in which the structure and magnetotransport properties of the manganite nanoclusters can be tuned by the tensile stress originati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
153
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(158 citation statements)
references
References 32 publications
1
153
2
Order By: Relevance
“…The T C values of the composite samples (359-368 K) change insignificantly. These results are quite different from other perovskite manganite-oxide composites [5,6,[10][11][12][13]18] that show significantly depressed T C values. The ferromagnetic ordering of LSMO is usually weakened by the addition of a secondary phase because of its chemical reaction with LSMO resulting in magnetic dilution [13].…”
Section: Methodscontrasting
confidence: 87%
See 1 more Smart Citation
“…The T C values of the composite samples (359-368 K) change insignificantly. These results are quite different from other perovskite manganite-oxide composites [5,6,[10][11][12][13]18] that show significantly depressed T C values. The ferromagnetic ordering of LSMO is usually weakened by the addition of a secondary phase because of its chemical reaction with LSMO resulting in magnetic dilution [13].…”
Section: Methodscontrasting
confidence: 87%
“…Since the LFMR values of pure RE 1-x A x MnO 3 perovskite maganites are insufficient for real applications, many groups have attempted to improve the LFMR effect by producing composites of manganites with second phases, such as insulating oxides [5][6][7][8][9][10][11][12][13], metals [14,15], polymers [16,17], and other manganites [18][19][20]. In comparison with a pure polycrystalline manganite, the perovskite manganite-oxide composites exhibited much improved LFMR effect, which was normally accompanied by a significant increase in their electrical resistivities and an abrupt decrease in their T C values.…”
Section: Introductionmentioning
confidence: 99%
“…Strain effects further modify the transport properties of manganite thin films by promoting long-range charge ordering. [27][28][29] We found that the resistance of films with thicknesses from 30 to 75 nm falls in the measurement range of our experimental setup. The transport properties of PCSMO films with various thicknesses are shown in Fig.…”
mentioning
confidence: 62%
“…C In functional oxides such as superconducting cuprates and ferromagnetic manganites, the investigation of electrically insulating columnar oxide defects embedded in the conducting matrix materials has experienced an increasing research activity in the past decade. 1,2 From the fundamental point of view, this activity was initiated by the exploration of the crystalline structure and elemental distribution at the interface between the columnar defects and the matrix material with the subsequent strain-and defect-induced modification of their electronic and magnetic properties. Elemental and electronic reconstructions at the interface between complex oxides with different functionalities are challenging phenomena to be explored.…”
mentioning
confidence: 99%